Effects of heat treatment on elastic constants of Cedar (Cedrus libani) wood - Güntekin, Ergün (Bursa Technical University, 2024)
The aim of this study was to evaluate the effects of heat treatment on the elastic constants of Cedar (Cedrus liba-ni) wood. Heat under atmospheric pressure at three different temperatures (150, 180 and 210 °C) and three differ-ent time levels (2, 5 and 8 hours) was applied to Cedar wood specimens and its Modulus of elasticity (EL, ER, ET) shear modulus (GLR, GLT, GRT) and Poisson’s ratios (?LR, ?LT, ?RL, ?RT, ?TL, ?TR) were evaluated by compression tests conducted on 20 x 20 x 60 mm samples using bi-axial extensometer. It was observed that the modulus of elastici-ty, shear modulus, and compression strength of the tested specimens were significantly affected by the temperature and time parameters of the heat treatment. Treatment of heat for low temperatures and short periods yielded some increase in modulus of elasticity but an increase in time and temperature resulted in a significant decrease. Heat treatment has a devastating influence on the shear modulus. Poisson’s ratios were less sensitive to the heat treat-ment. Heat treatment significantly alters the modulus of elasticity, shear modulus and compression strength of Cedar wood.

Bu çalışmanın amacı ısıl işlemin Sedir (Cedrus libani) odununun elastik sabitleri üzerindeki etkilerinin araştırılma-sıdır. Sedir odunu örnekleri atmosferik basınç altında üç farklı sıcaklıkta (150, 180 ve 210 °C) ve üç farklı zaman seviyesinde (2, 5 ve 8 saat) ısıya maruz bırakılmıştır. Elastikiyet modülü (EL, ER, ET), kesme modülü (GLR, GLT, GRT) ve Poisson oranları (?LR, ?LT, ?RL, ?RT, ?TL, ?TR) 20 x 20 x 60 mm numuneler üzerinde gerçekleştirilen basma testlerin-de çift eksenli ekstensometre kullanılarak belirlenmiştir. Test edilen numunelerin elastikiyet modülü, kesme modülü ve basma dirençleri ısıl işlemde sıcaklık ve zaman parametrelerinin önemli bir etkisi olduğu gözlemlenmiştir. Düşük sıcaklıklar ve kısa süreler için ısıl işlem, elastikiyet modülünde bir miktar artış sağlamış, ancak süre ve sıcaklığın artması, önemli ölçüde azalmaya neden olmuştur. Isıl işlem, kesme modülü üzerinde yıkıcı etkiye sahiptir. Poisson oranlarının ısıl işleme daha az duyarlı görülmüştür. Isıl işlem sedir odununun elastikiyet modülü, kayma modülü ve basma direncini önemli ölçüde değiştirmektedir.
Isıl işlemin Sedir (Cedrus libani) odununun elastik sabitleri üzerine etkileri
Keywords: Wood Physics and Mechanics; Ahşap Fiziği ve Mekaniği